Body size and first-winter survival of Red-crowned Crane Grus japonensis chicks. Issue 3 (3rd July 2019) - Takeda, Kohei F.; Kutsukake, Nobuyuki
ABSTRACT: An analysis of the biometrics of 187 individually marked Red-crowned Crane Grus japonensis chicks from Japan revealed that larger chicks were more likely to seen alive in their first-winter. Male chicks were larger than females but sex did not influence apparent survival, nor did brood size determine body size.